Characterization and kinetics of lipase inhibitory activity of streptomyces tendae - GURMEET SINGH; VENKATA KRISHNA BAYINENI; RAVI-KUMAR KADEPPAGARI (International Journal of Pharma and Bio Sciences, 2017)
The Streptomyces tendae was grown in the submerged cultures and the lipase inhibitory activity was assyed by using porcine pancreatic lipase. The inhibitory activity was extracted with ethyl acetate and purified by using HPLC. The inhibitory activity was characterized by UV-Vis spectrophotometry and LC-MS and its kinetic studies were done with Lineweaver-Burk plots. Lipase inhibitory activity was identified in the submerged cultures of S. tendae and its productivity was higher on the 7th day of fermentation. This inhibitory activity was eluted into the diethyl ether fraction while purifying on silica gel chromatogram and purified compound showed a single peak on HPLC. The compound showed the λmax of 254 nm, IC50 of 147.58 μg/ml and mass of 254 amu. Mass suggested it as a small molecule. Kinetic studies suggested that this molecule inhibits the porcine pancreatic lipase in a competitive manner.